Separation Of Xylose From Glucose Using Thinfilm Composite Membrane: A Study On Separation Performance And Fouling Properties - K. H., Mah; Wan Mohd Hafizuddin, Wan Yussof; Mazrul Nizam, Abu Seman; A. W., Mohammad (2015)
Separation of xylose from xylose-glucose solution using polyester thin-film composite (TFC) membrane was investigated using fractional factorial design with manipulation of interfacial polymerization (IP) factors between triethanoamine (TEOA) and trimesoyl chloride (TMC). In previous study, the relation between xylose separation factor and all affecting factors were developed in a model. In this present study, a new TFC membrane were produced from this model by the reaction between 4 % (w/v) TEOA concentration, 0.25 % (w/v) TMC concentration, reaction time of 44.85 minutes, pH 8, and curing at 60 ℃ for 30 minutes. Evaluation on the performance of TFC membrane shows that the xylose separation factor obtained in the study was 1.686, which has an error of 4.27 % compared to the predicted value. Membrane fouling has been studied for a course of 6 hours where the normalized relative flux (NRF) was at 16.61 (±3.53) %. From this value, irreversible fouling resulted in 11.02 (±5.60) % which might due to internal pore blockage of glucose and xylose. In contrast, reversible fouling of 5.59 % can be obtained back after cleaning with ultrapure water.